Impacts of malocclusion on the quality of life of children and adolescents: An integrative review (Research, Society and Development, 2021)
Malocclusions have a multifactorial etiology, and are characterized by the presence of irregularities in dental alignment and skeletal disharmonies, which end up compromising the aesthetics of the individuals' smiles, as well as the quality of life, especially in terms of psychosocial aspects and functional limitations. The review aimed to provide a synthesis of knowledge about the prevalence and consequences of malocclusion on the quality of life of children and adolescents, analyzing the literature regarding cases that show the problem of malocclusion and the intervention of the dental surgeon , aiming at a better quality of life for the patient. The present article is an integrative literature review type study with a qualitative character, where a bibliographic survey was carried out in the LILACS, SciELO and PubMed databases, to search the articles, the descriptors “Malocclusion”, “Quality of life”, “Temporomandibular joint”, “Children” and “Adolescent”. The inclusion criteria for sample selection were articles published in Portuguese and English, available in full, between 2010 and 2020, which portrayed the theme under study. Fifty-one articles were identified and, after reading, seventeen were selected that met the study theme. The analysis of the literature points out that, in addition to a possible change in craniofacial development, there is an association between malocclusion and socioeconomic, demographic and everyday factors that interfere with the individual's biological functions. In this sense, the research seeks to point out the harmony between oral health and the patient's well-being.